2012
DOI: 10.1007/978-3-642-34713-9_21
|View full text |Cite
|
Sign up to set email alerts
|

The Neural Dynamics of Visual Processing in Monkey Extrastriate Cortex: A Comparison between Univariate and Multivariate Techniques

Abstract: Abstract. Understanding the brain mechanisms underlying invariant visual recognition has remained a central tenet of cognitive neuroscience. Much of our current understanding of this process is based on knowledge gained from visual areas studied individually. Previous electrophysiology studies have emphasized the role of the ventral stream of the visual cortex in shape processing and, in particular, of higher level visual areas in encoding abstract category information. Surprisingly, relatively little is known… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
2
3
0
Order By: Relevance
“…In accordance with studies in monkeys (Cauchoix et al, 2012), it has been shown that faces can be discriminated from scrambled images within 80ms in magnetoencephalography sensors over the occipito-temporal cortex in humans (Dima et al, 2018). Angry versus neutral expressions are differentiated soon after (at 93ms) in the same sensor space and localized to the calcarine, lingual and inferior occipital cortices (Dima et al, 2018).…”
Section: How the Brain Processes Emotional Expressionssupporting
confidence: 76%
“…In accordance with studies in monkeys (Cauchoix et al, 2012), it has been shown that faces can be discriminated from scrambled images within 80ms in magnetoencephalography sensors over the occipito-temporal cortex in humans (Dima et al, 2018). Angry versus neutral expressions are differentiated soon after (at 93ms) in the same sensor space and localized to the calcarine, lingual and inferior occipital cortices (Dima et al, 2018).…”
Section: How the Brain Processes Emotional Expressionssupporting
confidence: 76%
“…We trained and tested a linear Support Vector Machine (SVM) classifier directly on pooled electrode potentials for every time point independently. This type of MVPA typically provides higher statistical power over univariate methods by pooling information across all electrodes, enabling reliable estimates of latencies from single trials [24]. Here we found that, indeed, reliable decoding of superordinate category information (animal vs. non animal) was possible from single trials under 100 ms post stimulus onset (M1: 92 ms, M2: 96 ms; Fig.…”
Section: Resultssupporting
confidence: 54%
“…For example, decoding analysis can result in earlier detection of differences in the signals (Cauchoix, Arslan, Fize, & Serre, 2012;Cauchoix et al, 2014), and the differences found by classifiers can differ from those found in components (Ritchie, Tovar, & Carlson, 2015).…”
Section: *** Figure 1 ***mentioning
confidence: 99%